2012
DOI: 10.1093/bib/bbs084
|View full text |Cite
|
Sign up to set email alerts
|

A survey on annotation tools for the biomedical literature

Abstract: New approaches to biomedical text mining crucially depend on the existence of comprehensive annotated corpora. Such corpora, commonly called gold standards, are important for learning patterns or models during the training phase, for evaluating and comparing the performance of algorithms and also for better understanding the information sought for by means of examples. Gold standards depend on human understanding and manual annotation of natural language text. This process is very time-consuming and expensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 62 publications
0
52
0
1
Order By: Relevance
“…11 A review of annotation tools Neves and Leser (2012) showed that BRAT was easy to use and could support both our annotation scheme and automatic preannotations. Configuration files were set-up to ensure that annotation labels were sorted in the order reflecting their relative frequency, based on a small sample of annotated texts.…”
Section: Annotation Toolsmentioning
confidence: 99%
“…11 A review of annotation tools Neves and Leser (2012) showed that BRAT was easy to use and could support both our annotation scheme and automatic preannotations. Configuration files were set-up to ensure that annotation labels were sorted in the order reflecting their relative frequency, based on a small sample of annotated texts.…”
Section: Annotation Toolsmentioning
confidence: 99%
“…We examined several options: WordFreak 7 [32], Callisto 8 , iAnnotate 9 [33], GATE 10 [34], UIMA [35], the tool created for the annotation of the EU-ADR corpus [16] and Knowtator 11 [36]. For detailed information about annotation tools for biomedical literature see [37]. Finally we chose the BRAT rapid annotation tool [25] for the following reasons:…”
Section: Definition and Annotation Guidelinesmentioning
confidence: 99%
“…Furthermore, the tools that support manual annotation should be intuitive to use, should include visualization of annotated text and should support easy-to-parse input and output formats (13, 14). To summarize, an annotation tool should be able to support a few or all stages listed above, but in a user-friendly interface.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, an annotation tool should be able to support a few or all stages listed above, but in a user-friendly interface. These general requirements were our main interest in developing an annotation interface because most curation systems currently available solve very specific problems and few of them can be used for multiple annotation tasks (14–16). …”
Section: Introductionmentioning
confidence: 99%